Design and CFD Analysis of Radial Inflow Turbines with 50 kW Power in Simple Organic Rankine Cycle with R1233zd(E) as Working Fluid - Fitrian Basri-13114011, Hafidz
The energy needs is increasing and are highly fulfilled with fossil fuel which is non-renewable and have negative impacts on the environment and health. Organic Rankine Cycle (ORC) is one of the renewable energy utilization systems that has the advantage of being able to convert energy from low temperature heat sources, one of which is waste heat. Turbine is one of the main components of the SRO. Thus research concerning the design of ORC turbine is necessary. The turbine is designed at condition of saturated vapor enter turbine at 85,286 ℃ 7,468 bar and exit at 3,395 bar. The methods used to design the turbine is meanline methods. The components to be designed are the rotor, nozzle, and volute. After that the resulting geometry are simulated using ANSYS CFX Compuational Fluid Dynamics (CFD) software. The CFD shows that the early design has appropriate power and efficiency. But there is a swirl at the turbine outlet due to the flow deviation at blade trailing edge. This swirl is affected by the camberline contour of the rotor. The camberline contour is then varied to get a design with a small swirl angle (<5 Ã‚Â°). The final design is then simulated in off-design conditions. The resulting rotor design has rotor flow coefficient ϕR of 0.83, diameter of 15.71 cm with 14 blades, and camberline angle of 50,7Ã‚Â°. The nozzle uses the NACA 66-006 profile, stator flow coefficient ϕS of 0.95, and a number of 26 blades. The volute chosen is circular cross section with external flow type. Finally, a turbine design with a power of 49.6 kW, total-to-static efficiency of 89.1%, and a swirl angle of 5.9 Ã‚Â° at mass flow rate of 3.89 kg/s and a rotating speed of 15000 RPM is obtained. Further research of this topic can be performed such as utilizing losses model in calculation process to result more accurately predicted design performance. Keywords: ORC, working fluid, radial inflow turbine, CFD